Software FAIRness, Documentation and Development Practices in Potsdam Researchers’ GitHub Repositories - Devkate, Akshay; Lamprecht, Anna-Lena (Electronic Communications of the EASST, 2025)
This study examines GitHub repositories of researchers affiliated with organizations in Potsdam, aiming to analyze various aspects of software FAIRness, documentation quality, and software development practices. Our methodology builds upon the SWORDS pipeline that was initially developed to examine the GitHub repositories of researchers affiliated with Utrecht University for FAIRness-related parameters. Our extended version of the pipeline also collects information about the documentation available (project description, installation instructions, usage guides) and development practices followed (explicit requirements, use of continuous integration, use of linters, automated testing, comments at start of code files). Our results indicate a diverse range of adherence to FAIR principles and software development practices among the repositories. While some repositories exhibit exemplary practices with thorough documentation and robust community participation, others lack basic elements crucial for software reusability and interoperability. These findings highlight the need for enhanced training and resources to support researchers in adopting best practices of research software development.